Commercial Specialty Cut Flower Production: Harvest Systems - Stevens, Alan B. (My University, 1995)
This publication describes the harvest of specialty cut flowers.
MF2155_1995_09
Keywords: MF2155; Lawn and Garden; Equipment and Structures; MF